Evaluation of Pore Geometry and Saturation Degree Influence to Electrical Resistivity Dispersion: A Potential Application to Extract Porosity - Khairy , Hilfan (2012)
Surface conductivity is indicated by electrical resistivity dispersion in low water saturation. When evaluating surface conductivity, the pore geometry should be considered because large structure is easier to saturate rather than small structure. This work underlines the evaluation of pore geometry distribution and saturation degree of reservoir rock and its effect to electrical dispersion. It is found that pore radius distribution and porosity has a good correlation with electrical dispersion. The large structure reflects more electrical dispersion compare to small one. In high water salinity, surface conductivity occurs at low water saturation degree and vanishes with more water saturation addition. The promising result has obtained to estimate porosity from electrical resistivity dispersion.